Enhancing Postgraduate Learning and Teaching: Postgraduate Summer School in Dairy Science - Pietro Celi; Gianfranco Gabai; Massimo Morgante; Luigi Gallo (Veterinary Medicine International)
Dairy science is a multidisciplinary area of scientific investigation and Ph.D. students aiming to do research in the field of animal and/or veterinary sciences must be aware of this. Ph.D. students often have vast spectra of research interests, and it is quite challenging to satisfy the expectation of all of them. The aim of this study was to establish an international Ph.D. training program based on research collaboration between the University of Sydney and the University of Padova. The core component of this program was a two-week Postgraduate Summer School in Dairy Science, which was held at the University of Padova, for Ph.D. students of both universities. Therefore, we designed a program that encompassed seminars, workshops, laboratory practical sessions, and farm visits. Participants were surveyed using a written questionnaire. Overall, participants have uniformly praised the Summer School calling it a rewarding and valuable learning experience. The Ph.D. Summer School in Dairy Science provided its participants a positive learning experience, provided them the opportunity to establish an international network, and facilitated the development of transferable skills.